Smart UTB: An IoT platform for Smart Campus (2021)
The Internet of Things (IoT) aims to create applications to improve people’s quality of life using novel protocols, sensor networks, cloud computing, middlewares and other technologies. These applications can be used in several contexts such as industry, agriculture or smart cities. On university campuses, applications based on IoT can also be implemented. The applications can be focused on monitoring people’s behavior, smart buildings, or sustainable environments. Generally, IoT applications are not designed and developed in a standardized way. Besides that, university campuses do not have a platform to manage and deploy these applications easily. This work presents Smart UTB, an IoT platform designed by using the Industrial Internet Reference Architecture (IIRA) and focused in the management and deployment of IoT applications towards sustainability in a smart campus.